Life span adult faces: norms for age, familiarity, memorability, mood, and picture quality. - Kennedy KM; Hope K; Raz N (Experimental Aging Research)
Because faces are frequently used as stimuli in cognitive aging behavioral and neuroimaging studies, there is a need for a normed set of pictures reflecting age and ethnic diversity. Minear and Park (2004, Behavior Research Methods, Instruments, & Computers, 36, 630-633) provided a large database of face pictures from average, ethnically diverse individuals across the adult life span. The current study evaluated 180 pictures from that database. One hundred and eight participants (mean age 23) rated each picture on specific attributes: perceived age, familiarity of appearance, mood, memorability, and image quality. Because the pictures did not differ in any of the measured attributes, the authors provide three balanced sets of face stimuli to researchers desiring normed face stimuli free from age confounds.